Phosphorus facilitation and covariation of root traits in steppe species - Yu, Rui-Peng; Li, Xiao-Xi; Xiao, Zhi-Hua; Lambers, Hans; Li, Long (The New phytologist, 2020)
• Different phosphorus (P)-acquisition strategies may be relevant for species coexistence and plant performance in terrestrial communities on P-deficient soils. However, how interspecific P facilitation functions in natural systems is largely unknown. • We investigated the root physiological activities for P mobilization across 19 coexisting plant species in steppe vegetation, and then grew plants with various abilities to mobilize sorbed P in a microcosm in a glasshouse. • We show that P facilitation mediated by rhizosphere processes of P-mobilizing species promoted growth and increased P content of neighbors in a species-specific manner. When roots interacted with a facilitating neighbor, Cleistogenes squarrosa and Bromus inermis tended to show greater plasticity of root proliferation or rhizosheath acid phosphatase activity compared with other non-P-mobilizing species. Greater variation in these root traits was strongly correlated with increased performance in the presence of a facilitator. The results also show, for the first time, that P facilitation was an important mechanism underlying a positive complementarity effect. • Our study highlights that interspecific P-acquisition facilitation requires that facilitated neighbors exhibit a better match of root traits with a facilitating species. It provides a better understanding of species coexistence in P-limited communities.